1980
DOI: 10.1007/bf00584554
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone in vitro restores nephron Na?K-ATPase of distal segments from adrenalectomized rabbits

Abstract: Aldosterone, when added in vitro to defined nephron segments, dissected from adrenalectomized rabbits, restores the depressed Na+-K+-ATPase activity in the thick ascending limb of the loop of Henle and in the cortical collecting tubule within 1 h of incubation. The direct effect is specific and, as demonstrated for the cortical collecting tubule, dose-dependent. The time course of aldosterone-mediated Na+-K+-ATPase activation is compatible with the conjecture of changes in the enzyme lipid environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1
1

Year Published

1984
1984
2001
2001

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 11 publications
4
14
1
1
Order By: Relevance
“…As reported earlier (17)(18)(19), short term aldosterone (3 h) increased the maximal hydrolytic activity of the Na,K-ATPase by ϳ200% (ADX control, 323 Ϯ 80; ADX aldosterone, 940 Ϯ 150 pmol ATP ϫ mm Ϫ1 ϫ h Ϫ1 ; n ϭ 9; p Ͻ 0.01). We performed Western blotting to test whether or not this increase in enzyme activity could be explained by an increase in the cellular pool of the Na,K-ATPase.…”
Section: Short Term Aldosterone Increases In Vivo Nak-atpase Hydrolysupporting
confidence: 79%
See 1 more Smart Citation
“…As reported earlier (17)(18)(19), short term aldosterone (3 h) increased the maximal hydrolytic activity of the Na,K-ATPase by ϳ200% (ADX control, 323 Ϯ 80; ADX aldosterone, 940 Ϯ 150 pmol ATP ϫ mm Ϫ1 ϫ h Ϫ1 ; n ϭ 9; p Ͻ 0.01). We performed Western blotting to test whether or not this increase in enzyme activity could be explained by an increase in the cellular pool of the Na,K-ATPase.…”
Section: Short Term Aldosterone Increases In Vivo Nak-atpase Hydrolysupporting
confidence: 79%
“…Concerning the effect of aldosterone on the Na,K-ATPase, measurements performed two decades ago on cortical collecting ducts (CCD) of adrenalectomized rats have shown that aldosterone restores within 1-3 h the Na,K-ATPase hydrolytic activity V max and/or the number of ouabain binding sites (17)(18)(19)(20)(21). The nature of this effect was not known because the data could not distinguish between the possibilities that additional Na ϩ pump units are synthesized, that Na ϩ pumps are activated in situ, or that Na ϩ pumps are recruited/translocated from an intracellular pool to the cell surface.…”
mentioning
confidence: 99%
“…Adrenalectomy reduces the activity of Na,K-ATPase in both the cortical and medullary segments of the thick ascending limb (34)(35)(36)(37)(38)(39)(40)(41). Although early studies indicated that aldosterone was capable of increasing the activity of Na,K-ATPase after adrenalectomy (36,39,40), more recent studies have shown that dexamethasone but not aldosterone increases enzyme activity (34,35,38 (6) did not observe an effect of an aute infusion of aldosterone on potassium reabsorption in the loop of Henle. This latter observation contrasts with the results in the present study, in which chronic aldosterone treatment stimulated potassium reabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…Horster and co-workers demonstrated that adrenalectomy caused a decrease in Na-K-ATPase in both thick ascending limb and collecting duct of rabbits (1). Aldosterone, when added in vitro to these nephron segments, restored Na-KATPase activity to normal within 1 h of incubation in both thick ascending limb and cortical collecting tubule.…”
Section: Introductionmentioning
confidence: 99%